Fibrinogen Coating Density Affects the Conformation of Immobilized Fibrinogen: Implications for Platelet Adhesion and Spreading - Moskowitz, Keith A.; Kudryk, Bohdan; Coller, Barry S. (Thrombosis and Haemostasis, 1998)
Adhesion of platelets to immobilized fibrinogen appears to play an important role in a variety of physiologic and pathologic phenomena. We previously observed that the fibrinogen concentration used to coat polystyrene wells affected the morphology and distribution of GP IIb/ IIIa receptors on the surface of platelets adherent to the fibrinogen. One possible explanation for these differences is that fibrinogen immobilized at high density adopts a different conformation than fibrinogen immobilized at low density. To address this possibility, we studied the binding of a panel of anti-fibrinogen monoclonal antibodies (mAbs) to fibrinogen immobilized at different coating densities. Three different patterns of binding were observed: 1) a linear increase in binding to wells coated with 1-10 μg/ml fibrinogen, followed by a lesser increase or plateau at higher fibrinogen concentrations (mAbs Fd4-4E1, Fd4-7B3, 1D4, 4-2); 2) minimal reactivity at all fibrinogen concentrations (mAbs GC4-1A12, 2C34); 3) a biphasic response, with a linear increase up to 10 μg/ml fibrinogen and then a significant decline in binding at higher fibrinogen concentrations (mAbs 311, 31A9, FPA 19/7, 9C3, 1C5-A5/2, 44-3). The patterns of mAb binding to fibrinogen immobilized from plasma were similar. Most mAbs that demonstrated a biphasic response bound poorly or not at all to soluble fibrinogen, while mAbs that demonstrated a linear/plateau response were able to bind soluble fibrinogen. At equal surface densities, mAbs that bound biphasically, particularly mAb 1C5-A5/2, were more reactive to urea-denatured than native fibrinogen. mAbs 1C5-A5/2 and 44-3 are specific for γ 1-78 and 95-265, respectively, suggesting that the fibrinogen γ-chain may be sensitive to changes in conformation induced by immobilization. In summary, these data suggest that fibrinogen immobilized at 1-10 μg/ml adopts a conformation unlike soluble fibrinogen, while fibrinogen immobilized at >30 μg/ml adopts a more solution-like conformation. These differences in fibrinogen conformation may partially account for the ability of platelets to bind to immobilized fibrinogen without the addition of agonist, as well as the differences in spreading and GPIIb/IIIa distribution on platelets adherent to high- versus low-density immobilized fibrinogen.